Effect of cold ischaemia time on outcome after living donor renal transplantation. Issue 9 (1st June 2016) - Nath, J; Hodson, J; Canbilen, S W; Al Shakarchi, J; Inston, N G; Sharif, A; Ready, A R
Abstract: Background: The aim of the present study was to determine the effects of cold ischaemia time (CIT) on living donor kidney transplant recipients in a large national data set. Methods: Data from the National Health Service Blood and Transplant and UK Renal Registry databases for all patients receiving a living donor kidney transplant in the UK between January 2001 and December 2014 were analysed. Patients were divided into three groups depending on CIT (less than 2 h, 2–4 h, 4–8 h). Risk-adjusted outcomes were assessed by multivariable analysis adjusting for discordance in both donor and recipient characteristics. Results: Outcomes of 9156 transplants were analysed (CIT less than 2 h in 2662, 2–4 h in 4652, and 4–8 h in 1842). After adjusting for confounders, there was no significant difference in patient survival between CIT groups. Recipients of kidneys with a CIT of 4–8 h had excellent graft outcomes, although these were slightly inferior to outcomes in those with a CIT of less than 2 h, with risk-adjusted rates of delayed graft function of 8·6 versus 4·3 per cent, and 1-year graft survival rates of 96·2 versus 97·1 per cent, respectively. Conclusion: The detrimental effect of prolonging CIT for up to 8 h in living donation kidney transplantation is marginal. Abstract : OK for 4 hours